1999
DOI: 10.1038/sj.sc.3100766
|View full text |Cite
|
Sign up to set email alerts
|

The risk of paraplegia through medical treatment

Abstract: In the Orthopedic University Hospital of Heidelberg (section Orthopedics II, treatment and rehabilitation of paraplegics), 21 patients with iatrogenic paraplegia were treated between 1968 and 1991. Paraplegia occurred in nine cases after procedures close to the spinal cord. In 12 cases paraplegia complicated medical treatment. Procedures close to the spinal cord, such as laminectomy, vertebrotomy, spondylodesis, and peridural anaesthesia, involve the risk of mechanical damage to the spinal cord, the level of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…This study reported four complications, including asymptomatic hypotension after neurolysis, retroperitoneal abscess after celiac plexus block, and severe self-limited post-procedural pain in two patients after celiac plexus block [ 50 ] . Reports of retroperitoneal bleed and abscess [ 51 ] , urinary retention [ 36 ] , hiccoughing [ 52 ] , bowel perforation, gastroparesis [ 53 ] , hemorrhagic gastritis [ 54 ] , loss of anal and bladder sphincter function [ 42 ] , ejaculatory failure [ 55 ] , anterior spinal artery syndrome and paraplegia [ 27,30,44 ] , aortic dissection [ 56 ] , and aortic pseudoaneurysm [ 57 ] have also been described.…”
Section: Complicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…This study reported four complications, including asymptomatic hypotension after neurolysis, retroperitoneal abscess after celiac plexus block, and severe self-limited post-procedural pain in two patients after celiac plexus block [ 50 ] . Reports of retroperitoneal bleed and abscess [ 51 ] , urinary retention [ 36 ] , hiccoughing [ 52 ] , bowel perforation, gastroparesis [ 53 ] , hemorrhagic gastritis [ 54 ] , loss of anal and bladder sphincter function [ 42 ] , ejaculatory failure [ 55 ] , anterior spinal artery syndrome and paraplegia [ 27,30,44 ] , aortic dissection [ 56 ] , and aortic pseudoaneurysm [ 57 ] have also been described.…”
Section: Complicationsmentioning
confidence: 98%
“…The neurolytic-induced vasospasm of the artery of Adamkiewicz may occur secondary to compromised perfusion due to surrounding tissue edema or by direct contraction of the arterial muscle wall [45][46][47] . Paraplegia may also result from direct injection of neurolytic agents into the artery of Adamkiewicz or radicular artery [ 27,29,44,48 ] . Even when CPB neurolysis has been performed under direct visualization by an open anterior approach, paraplegia has been a complication likely because of the close anatomical proximity of the celiac plexus to the artery of Adamkiewicz [ 49 ] .…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinical work, many iatrogenic reasons, especially spinal injury, may cause SCI. Bacher's study [3] showed that 42.8% (9/21) patients with iatrogenic SCI were related to operations close to the spinal cord, and the remaining 57.2% (12/21) were caused by ischemia or toxin mechanisms. There iatorgenic injuries were unexpected in most cases.…”
Section: Introductionmentioning
confidence: 98%
“…Direct injection of foreign sub-stances into the radicular arteries may also lead to spinal-cord infarction and paraplegia. 2,3 Several recent articles have detailed the adverse events associated with transforaminal steroid injections, including rare but catastrophic spinal-cord infarction and death. [4][5][6] Current data are insufficient to allow estimation of the incidence and prevalence of these catastrophic complications, but several recent reports have proposed guidelines for cervical transforaminal steroid injections.…”
mentioning
confidence: 99%